Manajemen Waktu Dalam Al-Qur’an dan Implikasinya terhadap Efektifitas Pembelaran Pendidikan Islam - Faruq Abdur Rouf; Ahmad Thib Raya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Time management is a vital aspect of Islamic education that influences learning effectiveness and the development of students’ discipline. In the Qur’anic perspective, time is regarded as a divine trust that must be managed wisely to achieve balance between spiritual and academic activities. This study aims to analyze the Qur’anic concept of time management and its implications for the effectiveness of Islamic education. The research employed a library-based method using thematic analysis of Qur’anic verses related to time, supported by empirical findings from nationally accredited Islamic education journals. The results indicate that Qur’anic time management emphasizes values of faith, consistency, productivity, and orderliness in learning activities. Implementing these principles within Islamic educational institutions has been shown to enhance learning discipline, time efficiency, and students’ spiritual balance. Moreover, Qur’anic time management strengthens an academic culture centered on blessing (barakah), work ethics, and moral responsibility. Therefore, Qur’anic-based time management can serve as a strategic model to improve learning quality and professional conduct among educators in contemporary Islamic education systems.